Síndrome visual informático en trabajadores de un centro de atención oftalmológico en Perú - Sánchez-Huamash, Claudia M. (2024)
Objective: To estimate the frequency of computer vision syndrome (CVS) in workers of an ophthalmologic care center in Peru. The secondary objective was to explore factors associated with CVS in these workers. Materials and methods: This is a descriptive cross-sectional study, which was performed during February and March 2024, in 240 workers of an ophthalmologic center in Peru. The main variable was CVS and it was assessed using the Computer Vision Syndrome Questionnaire (CVS-Q). Results: The median number of hours of daily use of electronic devices at work was 7 hours (interquartile range 5.5 to 8 hours). Nearly fifty-one percent (50.8%) of workers had CVS. The prevalence of CVS in men was 32% lower compared to the prevalence of CVS in women (aPR=0.68; 95% CI= 0.52 to 0.90; p=0.007). For each hour of work per week, the prevalence of SVI decreased by 2% (PRa=0.98; 95% CI= 0.950 to 0.998; p=0.031). Workers who had ophthalmologic disease had a 31% higher prevalence of SVI than those who did not (PRa=1.31; 95% CI= 1.03 to 1.66; p=0.027). Conclusions: About half of the workers in eye care centers have SVI, being male and working more hours per week is associated with lower SVI, but having underlying eye disease is associated with higher SVI.